2017
DOI: 10.1038/s41598-017-04192-9
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the biological aging of titanium using a wet storage method after ultraviolet treatment

Abstract: We evaluated whether the biological activity of the surface of titanium, when stored in an aqueous solution after ultraviolet (UV) treatment, is comparable to that of the surface immediately after UV treatment. We subjected Grade IV titanium discs with machined surfaces to UV radiation for 15 min and then tested them immediately and after storage for 28 days, with and without distilled H 2 O (dH 2 O). We evaluated the surface characteristics using surface profiling, contact angle analysis, X-ray photoelectron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Therefore, the amount of hydrocarbon adsorbed on TiO 2 from the time of manufacture to the time of implantation is crucial in determining the initial affinity level for osteoblasts. Choi et al [59] observed larger spindle-shaped MC3T3-E1 with extended actin filaments on the UV-treated surface of titanium stored in distilled water prior to their experiment. To date, the dental implant system with a SLActive ® surface (Institute Straumann AG, Basel, Switzerland) is the only implant system that is rinsed with nitrogen to prevent exposure to air and stored in a glass ampoule containing saline solution (0.9% sodium chloride) following manufacture.…”
Section: Titanium Surface Contaminationmentioning
confidence: 93%
“…Therefore, the amount of hydrocarbon adsorbed on TiO 2 from the time of manufacture to the time of implantation is crucial in determining the initial affinity level for osteoblasts. Choi et al [59] observed larger spindle-shaped MC3T3-E1 with extended actin filaments on the UV-treated surface of titanium stored in distilled water prior to their experiment. To date, the dental implant system with a SLActive ® surface (Institute Straumann AG, Basel, Switzerland) is the only implant system that is rinsed with nitrogen to prevent exposure to air and stored in a glass ampoule containing saline solution (0.9% sodium chloride) following manufacture.…”
Section: Titanium Surface Contaminationmentioning
confidence: 93%
“…It has been determined that the zeta potential of a biphasic calcium composite material is approximately À20.4 mV 172 and of nonmodified titanium around À10 mV. 173 Usually it is accepted that the increase of the negativity of the zeta potential of an implant allows a more favorable integration of the material into the tissue (e.g. ref.…”
Section: Biocompatibility and Zeta Potentialmentioning
confidence: 99%
“…Induced aspects involve the hierarchical structure of threads, screw pitch, concave grooves generated by sandblasting (in the range of 5 to about 70 μm), and pores of different shapes created by acid etching (in the range of several hundred nanometers up to 3 μm). This combination naturally leads to hydrocarbon adsorption (Att et al, ; Choi et al, , ) and a wetting behavior that, as explained in basic teaching of wettability science (Cassie & Baxter, , Dettre & Johnson Jr, , Wenzel, , ), is magnified by topographic details, leading to hydrophobic implant surfaces and large contact angle hysteresis on aging, as nicely described by Rupp et al (). Within these boundaries, prevention of hydrocarbon adsorption by wet storage (Baier & Meyer, ) or removal of adsorbed hydrocarbons by discharge techniques just before usage (Canullo et al, ; Choi et al, , ) stop or reverse the natural trend and provide high‐energy surfaces whose hydrophilicity is further enhanced by capillary wicking into grooves and pores.…”
Section: Discussionmentioning
confidence: 89%
“…In the case of titanium dental implants, the basic determinant of excess specific surface free energy, that is, the surface chemical composition, combines with the other properties that affect macroscopic wetting behavior and capillary rise, that is surface microtopography and thread size and shape (Rupp, Scheideler, Rehbein, Axmann, & Gels‐Gerstorfer, ), yielding increasingly hydrophobic surfaces as time from production goes bay. This behavior has been defined “biological aging” (Att et al, ; Choi et al, , ), with a view to its biological effects. Its cause, however, is plainly chemical–physical, as just discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation